Utility of non‐contrast head computed tomography in poisoned patients. (13th March 2021) - McNulty, Richard; Bandaranayake, Lashnika; Wong, Timothy; Garner, Alex; Tahmid, Farhan; Symes, Emily; Mohammad, Mohammad; Salter, Mark; Gunja, Naren
Abstract: Objective: To investigate the utility of non‐contrast head computed tomography (CT) in poisoned patients. Methods: A retrospective cohort study of patients referred to a toxicology unit between August 2010 and December 2017. Our database yielded patients who underwent head CT at presentation to the ED. Pre‐specified information was compiled from the medical records. Results: There were 6261 presentations of which 1142 underwent head CT (17%). Median age was 41 years, and 437 (38%) were female. There were 492 (43%) recreational ingestions and 466 (41%) deliberate self‐poisonings. The commonest agents were sedatives 376 (33%) and opioids 282 (24%); 334 (29%) cases were intubated. Signs of head injury were found in 153 cases (13%) and focal neurological signs in 68 (6%). No acute pathology was reported in 884 head CTs (77%), chronic changes in 193 (17%) and incidental findings in 26 (2%). Acute pathology was found in 39 (4%) patients: 15 with hypoxic‐ischaemic injury, three infarctions, nine with intra‐cranial haemorrhage, 11 facial bone fractures and one retro‐bulbar haematoma. No patient required an immediate surgical intervention, and only one patient had a change to clinical treatment. Acute head CT pathology was associated with at least one of the following clinical features: need for intubation, signs of head injury, seizure, headache, and unexpected neurological signs. Conclusion: Non‐contrast head CT is a low‐yield investigation in patients presenting with poisoning. Consideration should be given as to whether the clinical presentation is consistent with the expected toxidrome and whether the patient would benefit from head CT. Abstract : Non‐contrast head computed tomography is a common investigation in poisoned patients. Here we show that it is unlikely to change treatment and is not without adverse events.